Nutrient cycling in agro-ecosystems - Tivy, Joy (1987)
The nutrient cycle in the unmanaged ecosystem is compared with that in the agroecosystem; and the role and relative importance of soil organic matter, organic and inorganic fertilizers as sources of nutrient inputs into agro-ecosystems are analysed. This is followed by an assessment of the efficiency with which nitrogen, phosphorus, potassium, liming bases and micro-nutrients are cycled in agroecosystems. Finally, the characteristics of nutrient budgets and nutrient cycles in extensive, intensive and intermediate agro-ecosystems are summarized and the environmental implications of the very open agro-ecosystem noted.